Hybridization of woven kenaf and unidirectional glass fibre roving for unsaturated polyester composite - Balakrishnan, Thinesh Sharma; Sultan, Mohamed Thariq Hameed; Shahar, Farah Syazwani; Nayak, Suhas Yeshwant; Md Shah, Ain Umaira; Sebaey, Tamer Ali; Basri, Adi Azriff (Springer Science and Business Media Deutschland GmbH, 2024)
This is a study on the mechanical properties of kenaf/glass-reinforced polyester composites intended for use in structural profiles with a wall thickness by max. 6 mm. Mechanical properties such as tensile, compression, bending and interlaminar shear stress were investigated by comparing the hybrid variants with the pure fibreglass variant. According to the study, woven kenaf/unidirectional glass roving (WK/UG) alternate recorded the highest tensile properties among hybrid samples. It demonstrated a decrement of about 8.2% of the tensile strength (404.54 MPa) and 10.7% of tensile modulus (24.54 GPa) compared to conventional fibreglass samples. Alternating WK/UG samples demonstrated higher compressive strength (417.15 MPa) compared to other hybrid specimens, recording a slight decrease at 6.09% compared to pure fibreglass composites. The highest bending properties were also observed in hybrid alternate WK/UG samples among other hybrid laminates with only a decrement of 4.13% in modulus of rupture (456.33 MPa) and 1.9% in modulus of elasticity (14.49 GPa) when compared to the control specimen. The ILSS of hybrid composites 2WK/3UG/2WK (30.97 MPa) and WK/UG alternate (34.90 MPa) showed good agreement with the pure fibreglass (42.33 MPa) composites. Using SEM images, tensile fractured specimens were examined to comprehend composites’ failure mechanism and interfacial adhesion. Overall, woven kenaf/unidirectional glass roving alternate sequence is chosen as a potential alternative in developing structural profiles for moderate load-bearing structural applications. In contrast, 3WK/UG/3WK with a higher kenaf to glass ratio demonstrate potential in low load-bearing structural profile applications.